Comprehensive analysis of HSF genes from celery (Apium graveolens L.) and functional characterization of AgHSFa6-1 in response to heat stress - Li, Mengyao; Zhang, Ran; Zhou, Jin; Du, Jiageng; Li, Xiaoyan; Zhang, Yong; Chen, Qing; Wang, Yan; Lin, Yuanxiu; Zhang, Yunting; He, Wen; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2023)
High temperature stress is regarded as one of the significant abiotic stresses affecting the composition and distribution of natural habitats and the productivity of agriculturally significant plants worldwide. The HSF family is one of the most important transcription factors (TFs) families in plants and capable of responding rapidly to heat and other abiotic stresses. In this study, 29 AgHSFs were identified in celery and classified into three classes (A, B, and C) and 14 subgroups. The gene structures of AgHSFs in same subgroups were conserved, whereas in different classes were varied. AgHSF proteins were predicted to be involved in multiple biological processes by interacting with other proteins. Expression analysis revealed that AgHSF genes play a significant role in response to heat stress. Subsequently, AgHSFa6-1, which was significantly induced by high temperature, was selected for functional validation. AgHSFa6-1 was identified as a nuclear protein, and can upregulate the expression of certain downstream genes (HSP98.7, HSP70-1, BOB1, CPN60B, ADH2, APX1, GOLS1) in response to high-temperature treatment. Overexpression of AgHSFa6-1 in yeast and Arabidopsis displayed higher thermotolerance, both morphologically and physiologically. In response to heat stress, the transgenic plants produced considerably more proline, solute protein, antioxidant enzymes, and less MDA than wild-type (WT) plants. Overall, this study revealed that AgHSF family members perform a key role in response to high temperature, and AgHSFa6-1 acts as a positive regulator by augmenting the ROS-scavenging system to maintain membrane integrity, reducing stomatal apertures to control water loss, and upregulating the expression level of heat-stress sensitive genes to improve celery thermotolerance.